Tailored Therapy in Lung Cancer - George Rakovich; Lise Tremblay (Canadian Respiratory Journal)
Historically, all non-small cell lung cancers were essentially grouped together and considered to be a single disease. However, it is now recognized that non-small cell lung cancer actually comprises a genetically diverse group of tumours. This, in turn, affords a new opportunity for the development of effective treatments tailored to individual tumours and patients. Advances in molecular biology have made possible the development of drugs against specific molecular targets on cancer cells, most notably the tyrosine kinase inhibitors. The relevant literature and current practice guidelines are discussed. In addition, other related areas of active investigation, including tumour vaccines and pharmacogenetics, are briefly reviewed.